Syndromic Disorders Caused by Disturbed Human Imprinting - Diana Carli; Evelise Riberi; Giovanni Battista Ferrero; Alessandro Mussa (Galenos Yayincilik, 2020)
Imprinting disorders are a group of congenital diseases caused by dysregulation of genomic imprinting, affecting prenatal and postnatal growth, neurocognitive development, metabolism and cancer predisposition. Aberrant expression of imprinted genes can be achieved through different mechanisms, classified into epigenetic - if not involving DNA sequence change - or genetic in the case of altered genomic sequence. Despite the underlying mechanism, the phenotype depends on the parental allele affected and opposite phenotypes may result depending on the involvement of the maternal or the paternal chromosome. Imprinting disorders are largely underdiagnosed because of the broad range of clinical signs, the overlap of presentation among different disorders, the presence of mild phenotypes, the mitigation of the phenotype with age and the limited availability of molecular techniques employed for diagnosis. This review briefly illustrates the currently known human imprinting disorders, highlighting endocrinological aspects of pediatric interest.